2014
DOI: 10.1007/s11064-014-1418-8
|View full text |Cite
|
Sign up to set email alerts
|

Effective Suppression of Acrylamide Neurotoxicity by Lithium in Mouse

Abstract: The primary objective of this investigation was to assess the neuroprotective efficacy of lithium in an acrylamide (ACR)-induced neuropathy model in mice. In this study, Kunming male mice were administered ACR (25 mg/kg bw, i.p. once a day) with or without lithium (25 mg/kg bw, i.p. once a day) for 2 weeks. All ACR-administered mice exhibited severe symptoms of neuropathy. We found that treatment with lithium effectively alleviated behavioral deficits in animals elicited by acrylamide. Interestingly, the reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Previous studies have reported that ACR inhibits neurogenesis through the activation of the GSK3β signaling pathway. 40 By comparison, taurine has been shown to exert an antidepressant-like effect, influencing depression-related signaling cascades in the hippocampus by altering the levels of phosphorylated GSK3β. 41 In addition, taurine has an impact on various signaling pathways and the gene expression of many proteins, including those involved in the Akt/PKB and PI3K/Akt signaling pathways, especially GSK3β phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that ACR inhibits neurogenesis through the activation of the GSK3β signaling pathway. 40 By comparison, taurine has been shown to exert an antidepressant-like effect, influencing depression-related signaling cascades in the hippocampus by altering the levels of phosphorylated GSK3β. 41 In addition, taurine has an impact on various signaling pathways and the gene expression of many proteins, including those involved in the Akt/PKB and PI3K/Akt signaling pathways, especially GSK3β phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that ACR inhibits neurogenesis through the activation of the GSK3β signaling pathway. 40 By In (a), a P < 0.05, compared with the control group; b P < 0.05, compared with the ACR group; c P < 0.05, compared with the ACR + TAU group. In (b), a P < 0.05, compared with the control group; b P < 0.05, compared with the TAU group; c P < 0.05, compared with the TAU + MK-2206 group; d P < 0.05, compared with the ACR group; e P < 0.05, compared with the ACR + MK-2206 group; f P < 0.05, compared with the ACR + TAU group.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that 'green tea extract is a potent antioxidant antidote for the AA toxic effects upon testicular function'. Song et al (2014) Effective suppression of AA neurotoxicity by lithium in mouse.…”
Section: Yassa Et Al (2014)mentioning
confidence: 99%
“…Similar findings have been reported in Drosophila melanogaster (fruit fly) studies (Prasad and Muralidhara, , ). Glycogen synthase kinase 3 beta (GSK‐3β) is activated by ACR treatment, causing a lack of neurogenesis in the hippocampus (Song et al ., ), and curcumin was shown to inhibit this enzyme (Aggarwal and Sung, ; Bustanji et al ., ). Although no study has looked into both ACR toxicity and GSK‐3β inhibition by curcumin, it seems reasonable to assume that this mechanism of action contributes to the protective effect of curcumin, especially when considering that lithium, another GSK‐3β inhibitor, also protects against ACR (Song et al ., ).…”
Section: Introductionmentioning
confidence: 99%